CP-105 Cost effectiveness of ticagrelor for cardiovascular prevention in patients with acute coronary syndromes and low-dose aspirin in Spain. (24th February 2014) - Molina, E; Nieto, P; Rodríguez, P; Martínez, E; Verdejo, F; Cifuentes, S
Abstract : Background: The efficacy and safety of ticagrelor versus clopidogrel in patients with acute coronary syndromes (ACS) are well documented in the PLATO trial. Ticagrelor has been associated with better outcomes in patients taking low doses of acetylsalicylic acid (ASA) (75–150 mg). Purpose: The aim of this study was to assess the long-term cost effectiveness of treating ACS patients for 12 months with ticagrelor compared with clopidogrel in a low-dose ASA cohort in Spain. Materials and methods: Event rates and health-related quality of life during 12 months of treatment were estimated from PLATO in a low-dose ASA cohort (≤ 150 mg) for all ACS patients with either ticagrelor or clopidogrel. Health-related costs were obtained from Spanish published literature. Beyond 12 months, quality-adjusted survival and costs were estimated conditional on whether a non-fatal myocardial infarction (MI), non-fatal stroke, no MI or stroke occurred during the 12 months of treatment. Lifetime costs, life years gained (LYG), and quality-adjusted life years (QUALYs) were estimated for both treatment strategies. Incremental cost-effectiveness ratios were presented from the Spanish health system perspective in 2013 Euros applying a macro-costing approach based on published literature and life tables from a Spanish setting. Results: Treatment with ticagrelor was associated with increased healthcare costs of 1268 €, a LYG gain of 0.1871 and a QALY gain of 0.1504 compared with clopidogrel, yielding a cost per LYG gained of 6774 € and a cost per QUALY gained of 8428 €. Sensitive analyses showed consistent results in all scenarios. Conclusions: Based on clinical and health-economic evidence from the PLATO study, treating patients with ticagrelor for 12 months is associated with a cost per QALY below generally accepted thresholds for cost effectiveness in Spain. No conflict of interest.